Pengembangan Media Mobile Learning Menggunakan Aplikasi Articulate Storyline Pada Materi Sistem Peredaran Darah Pada Manusia Di Kelas XI SMA Negeri 1 Amurang - Natasya Ayu Muaja Wungow; Orbanus Naharia; Jantje Ngangi (International Forum of Researchers and Lecturers, 2023)
This research aims to produce a mobile learning media product using an articulate storyline application on human circulatory system material that is feasible and can be used by students at SMA Negeri 1 Amurang. Mobile learning media using the articulate storyline application is needed by school teachers to help during the learning process. This type of research is Research and Development / R&D development research using the ADDIE model. This model, as the name suggests, is Analysis, Design, Development, Implementation and Evaluation. The test instrument in this research is the product validity results from material and media experts. The data analysis techniques used are qualitative and quantitative approaches. The results of this research: 1) Development of mobile learning media using the articulate storyline application on the circulatory system material. 2) The quality of mobile learning aids on human circulatory system material is excellent. The assessment results from learning material experts obtained a feasibility percentage score of 85% for the very valid category. The assessment results from learning media experts obtained a feasibility percentage score of 89.9% for the very valid category. The response of students in class XI MIPA was in the perfect/exciting criteria with a percentage of 87.5%. It was concluded that the mobile learning media using the articulate storyline application on the circulatory system material at SMA Negeri 1 Amurang is very suitable to be used as a source of teaching material in the learning process.